PEMANFAATAN MEDIA BOOKLET TERHADAP PENINGKATAN PENGETAHUAN IBU MENYUSUI TENTANG PIJAT OKSITOSIN - Ria Gustirini (AKADEMI KEBIDANAN HARAPAN MULYA PONOROGO, 2021)
Breast milk production in the first days of childbirth becomes an obstacle for mothers in breastfeeding. Oxytocin massage is one way to overcome the improper production of breast milk. Knowledge or cognitive is a very important domain in shaping one's actions (ovent behavior). Health education can use various media, one of which is through the use of booklets. The aims: to analyze the effect of using booklet media on breastfeeding mothers' knowledge about oxytocin massage. The Method: This research was a quasi-experimental study using a pre test and posttest control design. Sampling in this study using purposive sampling technique. Some postpartum mothers who gave birth in January - May 2020 and met the inclusion criteria for a sample of 30 respondents who were divided into the treatment group and the control group. The statistical test used the independent t-test. Results: The results showed that there was a significant difference in increasing knowledge about oxytocin massage between the group that was given a booklet (treatment) and the group that was not given a booklet (control) with p value <0,05. Conclusion: The role of a midwife as a professional is indispensable in providing health education so that the use of various media as a means of conveying information is needed to increase maternal knowledge